American tegumentary leishmaniasis: epidemiological profile of reported cases in Brazil between the years 2009 to 2018 and considerations about aspects and manifestations of dental importance (Research, Society and Development, 2020)
American tegumentary leishmaniasis (ATL) is an infectious-parasitic disease of wide distribution worldwide that can affect cutaneous and mucous tissues, such as the nasal and oral mucosa, showing manifestations of dental interest. Since it is a public health problem, aimed to evaluate the epidemiological profile of ATL cases reported in Brazil, and addressing some considerations about their expressions of dental interest. Thus, this research is a retrospective and descriptive ecological study with a quantitative approach on the number of ATL cases reported in Brazil between the years 2009 to 2018. The data show that 209,129 cases were reported in this period. The majority affect male individuals, aged 20 to 39 years old, race/ethnicity mixed, low level of education and who live in rural areas, with the majority being notified in the Northern region. The cases are mostly recent, cutaneous form, autochthonous, diagnosed through clinical and laboratory parameters and evolution for healing. The results of this study allow us to estimate that although the national spread of ATL cases has shown some changes in its epidemiological profile, there is still a high prevalence, affecting mainly men with low income/education. In addition, the involvement of the mucous form through ulcerated and destructive lesions in the nasal and oral regions underscore the importance of the Dentists in the diagnosis and management of these injuries.